The elasticity of I think: Stretching its pragmatic functions - Zhang, Grace (De Gruyter Mouton, 2014)
I think (ITH) is commonly used in communication. Existing studies of its pragmatic functions focus on individual functions, but their interconnection has received little attention. This study looks into ITH functions from the refreshing perspective of language elasticity (Zhang, 2011). Drawn on naturally occurring data of institutional and often tension-prone discourse involving Australian customs officers and passengers, the study show a rare and rich insight into strategically elastic use of ITH. The local and global elasticity manifests as multi-trajectory and overlapping, with a non-linear nature. In responding to different communicative goals, the stretching trajectories move from the basic evaluative function (foregrounded in this study), upward to emphatic ITH (intensifying), downward to tentative and mitigating ITH (weakening), and sideways to discursive ITH (evolving). ITH functions are fluid, overlapping, complementary, and therefore co-exist. The implications of this study are that the elastic language warrants a non-discrete approach: we do not have to give up on "problematic" cases in identifying linguistic categories, the principle of elasticity may embrace these intriguing and exciting cases. The conceptualization of elasticity is probably an integral part of any adequate language research.